Screening Young Children for Latent Tuberculosis in England: Lessons Learned from the Field - Phipps, Emily; Clear, Anita; Holland, Margaret; Shahidi, Mitra; Tamne, Surinder; Cohen, Jonathan; Mearkle, Rachel; Morris, Jill (Journal of Pediatric Infectious Diseases, 2019)
Objective Tuberculosis (TB) can affect young children, resulting in serious disease at a young age or reactivation later in life. Identifying cases of latent TB infection (LTBI) in children exposed to active cases is important to prevent morbidity and mortality. There is currently limited guidance on appropriate testing methods in situations involving mass screening of children in low TB incidence settings such as England. This study describes case reports of two separate occasions in which nursery-age children in England underwent LTBI screening and explores the decisions involved in choosing the most appropriate test and screening process.Methods A literature search, review of health protection case and incident management notes, and interviews with key stakeholders were conducted.Results Two different tests—tuberculin skin testing and interferon gamma release assay—were used in each respective screening situation and the decision between the two was taken based on cohort, organizational, and index case risk factors. Screening took place in dedicated secondary care clinics. No cases of LTBI were identified from either screening incident.Conclusion Our study highlights the lack of definitive guidance for mass LTBI screening of young children and presents the approaches to decision making that can be adopted by others. Further research is required to test the approach suggested in this article and to ensure that evidence-based national guidance provides a consistent and effective approach to such incidents.
Keywords: tuberculosis; screening; diagnostics; clinical guidelines; public health